THE INFLUENCE OF LOCAL OWN-SOURCE REVENUE (PAD) ON THE FINANCIAL INDEPENDENCE OF REGENCIES/CITIES THROUGHOUT SUMATRA ISLAND - Sri Rizky; Chairil Akhyar; Ristati; Husaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study examines the influence of Local Own-source Revenue (PAD) and gross regional domestic product on regional financial independence in regencies/cities on Sumatra Island in 2020. This study uses secondary data in the form of budget realization reports published at the Directorate General of Fiscal Balance. The sample in this study consists of 154 regencies/cities throughout Sumatra Island. The data analysis method used is multiple linear regression using Eviews 12. The results partially indicate that Local Own-source Revenue (PAD) and gross regional domestic product have a positive and significant effect on regional financial independence in districts/cities on the island of Sumatra year 2020.